SEX, SEASON AND YEAR-WISE VARIATIONS IN QUANTITATIVE TRAITS OF RAlLY ECORACE, A WILD TASAR SILKWORM OF ANTHERAEA MYLITTA D. - MAHOBIA, G.P.; YADAV, G.S.; RAO, K.V.S.; VIJAYPRAKASH, N.B. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2009)
The ecorace ‘Raily’ of Antheraeamylitta D. is endemic to Bastar plateau of Chhattisgarh, India and is a eurythermic, wild, polyphagus, bivoltine in nature. It is mainly of Sal (ShorearobustaRoxb.) origin but also feeds on large number of secondary tasar flora. The present study evinces the morphometric variations in the quantitative traits of cocoons of seven ecopockets of two seasons and of two years i.e. of 1990 and 2000 recorded associated variations at an interval of a decade. The study conferred significant variations for the seven traits under study between the sexes and between the crops (p<O.01, df= 12) except for shell weight in 1st crop (p>O.05, df= 12). These traits presented no differences in pooled samples of both the sexes (p>O.05, df = 12; NS : Not significant). The seven traits uder study during the year .1990 and 2000 for the first and second crops surmised no differences within the sex and pooled samples of both the sexes ((p>O.05, df= I 2).